Photolysis of a Caged, Fast-Equilibrating Glutamate Receptor Antagonist, MNI-Caged γ-D-Glutamyl-Glycine, to Investigate Transmitter Dynamics and Receptor Properties at Glutamatergic Synapses - Palma-Cerda, Francisco; Papageorgiou, George; Barbour, Boris; Auger, Céline; Ogden, David (Frontiers in Cellular Neuroscience, 2018)
Fast uncaging of low affinity competitive receptor antagonists can in principle measure the timing and concentration dependence of transmitter action at receptors during synaptic transmission. Here we describe the development, synthesis and characterisation of MNI-caged γ-D-glutamyl-glycine, which combines the fast photolysis and hydrolytic stability of nitroindoline cages with the well-characterised fast-equilibrating competitive glutamate receptor antagonist γ-DGG. At climbing fiber-Purkinje cell (CF-PC) synapses MNI-caged γ-DGG was applied at concentrations up to 5 mM without affecting CF-PC transmission, permitting release of up to 1.5 mM γ-DGG in 1 ms in wide-field flashlamp photolysis. In steady-state conditions, photoreleased γ-DGG at 0.55-1.7 mM inhibited the CF first and second paired EPSCs by on average 30% and 60% respectively, similar to reported values for bath applied γ-DGG. Photolysis of the L-isomer MNI-caged γ-L-glutamyl-glycine was ineffective. The time-course of receptor activation by synaptically released glutamate was investigated by timed photolysis of MNI-caged-γ-DGG at defined intervals following CF stimulation in the second EPSCs. Photorelease of γ-DGG prior to the stimulus and up to 3 ms after showed strong inhibition similar to steady-state inhibition; in contrast γ-DGG applied by a flash at 3-4 ms post-stimulus produced weaker and variable block, suggesting transmitter-receptor interaction occurs mainly in this time window. The data also show a small and lasting component of inhibition when γ-DGG was released at 4-7 ms post stimulus, near the peak of the CF-PC EPSC, or at 10-11 ms. This indicates that competition for binding and activation of AMPA receptors occurs also during the late phase of the EPSC, due to either delayed transmitter release or persistence of glutamate in the synaptic region. The results presented here show first that MNI-caged-γ-DGG has properties suitable for use as a synaptic probe at high concentration and that its photolysis can resolve timing and extent of transmitter activation of receptors in glutamatergic transmission.